COMMUNICATION BASICS IN HADITH - Junaidi Junaidi (Proceeding International Seminar of Islamic Studies, 2021)
Communication is a basic need and part of basic human needs. Communication is like food that must exist in human life, without communication humans will die. On this basis, Islam as a religion that comes from God also pays attention to and provides guidance in communication. If traced, you will find many hadiths of the Prophet Muhammad that can be used as a basis for communication. In this paper, only 3 hadiths are presented as the basis of communication.Keywords: Communication and Hadith.